THE USE OF CAD SYSTEM IN THE INNOVATIVE METHOD OF TEACHING GRAPHIC DISCIPLINES (Journal of Information Technologies in Education (ITE), 2023)
The experience of online engineering and computer graphics education at the Ivano-Frankivsk National Technical University of Oil and Gas for engineering majors is considered. The problems of achieving project-oriented learning competencies in online mode are analyzed. The use of CAD systems is considered to ensure the graphic competencies provided by the "Engineering and Computer Graphics" course program in the online conditions of the organization of the educational process. As an example, "Sketching" (the IKG course topic) -  is considered, which is one of the most vulnerable to the achievement of graphic competencies in online learning. The result of this topic should be acquiring skills for creating a sketch from a part made of metal, gaining experience in measuring it, and determining the roughness of surfaces. This topic includes graphic works for sketching several details (cover, union nut, fitting, etc.). During off-line training in the classroom, each student is given a part made of metal, from which he determines all the parameters and attributes necessary for creating a sketch using the methods of measurement and visual inspection. The problems that arise during online training are not related to the creation of technical drawings but to the ability to obtain information from parts made of metal. The considered material gives reasons to assert that the development of CAD systems requires methodical material improvement to ensure students' acquisition of competencies related to their use. Also, the development of these systems makes it possible to use them not only as a subject of study by students but also to create methodological support for engineering graphics, which in turn expands the skills of their use by students.
Keywords: competence; engineering graphics; computer graphics; CAD system; learning process; online learning